A STOCHASTIC MODEL FOR THE TRAFFIC STREAM IN AN INTERSECTION - Suyono Suyono (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2004)
In this paper we discuss the probability distribution of the maximal number of persons that can safely cross the one-waytraffic stream in an intersection. The traffic stream is modelled as a renewal process and the number of persons that cancross the stream depends on the time interval between consecutive cars in the traffic stream. The results are presented inthe form of Laplace transforms which can be inverted numerically.